2022
DOI: 10.1021/acsami.1c24342
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Photoelectrode Interfaces for Solar Coupling of Lignin Oxidation with Biocatalytic C═C Bond Hydrogenation

Abstract: The pulp and paper manufacturers generate approximately 50 million metric tons of lignin per annum, most of which has been abandoned or incinerated because of lignin's recalcitrant nature. Here, we report bias-free photoelectrochemical (PEC) oxidation of lignin coupled with asymmetric hydrogenation of CC bonds. The PEC platform consists of a hematite (α-Fe 2 O 3 ) photoanode and a silicon photovoltaic-wired mesoporous indium tin oxide (Si/mesoITO) photocathode. We substantiate a new function of photoelectroac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Photoelectrochemical (PEC) systems can overcome this issue because mechanistically (photo)anodes serve as electron acceptors. 127–130 Ottone et al 27 reported ZnO materials for PEC regeneration of NAD + (Fig. 8c).…”
Section: Light-driven Biocatalytic Dehydrogenationmentioning
confidence: 98%
“…Photoelectrochemical (PEC) systems can overcome this issue because mechanistically (photo)anodes serve as electron acceptors. 127–130 Ottone et al 27 reported ZnO materials for PEC regeneration of NAD + (Fig. 8c).…”
Section: Light-driven Biocatalytic Dehydrogenationmentioning
confidence: 98%
“…Achieving an ideal morphology that can maximize charge generation and extraction using suitable materials and treatments is an efficient method to improve device efficiency. [ 30,31 ] Optimization of the active layer morphology needs to achieve suitable domain size, appropriate donor/acceptor (D/A) phase separation, and more reasonable crystallinity, as well as domain purity, for the achievement of efficient excitons dissociation and enhanced charge transport. [ 32,33 ] In this instance, the miscibility of the donor and acceptor is a critical factor in defining the quality of such active layer morphology.…”
Section: Introductionmentioning
confidence: 99%
“…To realize effective ex vivo bio-oxidoreductions, recently, the electrochemical NADH regeneration has emerged as an important method showing great potential in enzymatic valorization of biomass-derived molecules, such as lignin, α-ketoglutarate, ketoisophrone, and 2-methylcyclohexenone. This strategy exhibits remarkable advantages of trace by-product formation, ease of product separation, and the usage of renewable electricity as a power resource. A common limitation of electroenzymatic catalysis is the slow electron transfer efficiency between NAD + and the electrode, which further leads to low selectivity and poor stability . To overcome the challenges, the assembling of the Rh complex on the working electrodes provides an enlightened avenue in bioconversion .…”
Section: Introductionmentioning
confidence: 99%